2019
DOI: 10.1186/s13638-019-1388-2
|View full text |Cite
|
Sign up to set email alerts
|

Friend and POI recommendation based on social trust cluster in location-based social networks

Abstract: Friend and point-of-interest (POI) recommendation are two primary individual services in location-based social networks (LBSNs). Major social platforms such as Foursquare and Instagram are all capable of recommending friends or POIs to individuals. However, most of these social websites make recommendations only based on similarity, popularity, or geographical influence; social trust among individuals has not been considered in those recommendation system. Recently, trust relationship has been proved to be hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Analysis of data collected from LBSN platforms led DeScioli et al [13] to conclude that social connections are highly related to geographical distance. Zhu et al [14] clustered users based on social trust in formulating recommendations of potential friends. Chen and Li [15] developed a novel graph embedding method to find potential propagators and customers in LBSNs.…”
Section: Recommendation Systems Using Data Acquired From Lbsnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of data collected from LBSN platforms led DeScioli et al [13] to conclude that social connections are highly related to geographical distance. Zhu et al [14] clustered users based on social trust in formulating recommendations of potential friends. Chen and Li [15] developed a novel graph embedding method to find potential propagators and customers in LBSNs.…”
Section: Recommendation Systems Using Data Acquired From Lbsnsmentioning
confidence: 99%
“…Hence, we developed the Partners Finding Speed Up Algorithm to solve this problem. This algorithm reduces the computational load using the regressive SRS scores between candidate partners and q in Equation (14). The candidate partners are first arranged from smallest to largest according to their distance from query POI q.…”
Section: Partners Finding Speed Up Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The learned preferences are enhanced by the integration of the learning model with social influence. This work is similar to our work in the sense that it considers the notion of similar preferences among friends. Zhu et al (2019) proposed a trust prediction method based on identified trust clusters. The friends' recommendation is based on the trust value and the similarity among individuals.…”
Section: Related Workmentioning
confidence: 99%
“…To implement the proposed algorithm in this research, real-time and hybrid networks were used, and the results showed that the proposed algorithm has high accuracy for identifying communities and belonging to a node to a community. Zhu et al [35] focused on how various social networks, including Foursquare and Instagram, work. ese networks often use two methods, including Point-of-Interest (POI) discovery and friendly advice to make suggestions based on where people live.…”
mentioning
confidence: 99%